How does ballet training alter ankle tendinous morphology and hemodynamics in asymptomatic pre-professional dancers? An ultrasonographic study - Shih, W. S.; Wu, C. H.; Wang, T. G. (Journal of Science and Medicine in Sport, 2019)
Objectives: Among symptomatic dancers, sonographic abnormalities are common. Whether asymptomatic dancers have any abnormalities remains unknown. Some dancers became cyanosis over distal feet after ballet training. The hemodynamic changes at the feet in ballet are not clearly understood. Design: Cross-sectional study. Methods: In 25 dancers and 14 non-dancers, B-mode ultrasonography was used to measure cross-sectional areas (CSA) of tendons of deep posterior compartment muscles. Doppler ultrasonography was used to measure peak velocity (Vpeak) of posterior tibial artery in three ankle postures: the neutral position, passively and forced actively plantar flexion (en pointe). The big toe oxygen saturation was recorded in neutral position and during 1-min en pointe. Single-leg standing heel rise test was performed to represent the muscle function. Results: The CSA of FHL was larger in dancers (0.26 cm2 [0.20, 0.30] vs 0.21 cm2 [0.17, 0.24], p < 0.01), while other tendons were not different (all p > 0.05). Higher Vpeak was recorded in passively plantar flexion than in neutral position (p < 0.01, in both groups). The blood flow was undetectable during en pointe, more frequently in dancers (54.9% vs 14.3%, p < 0.01). Oxygen saturation decreased during en pointe more prominently in dancers (85% [80, 90] vs 94% [84, 97], p < 0.01). There was no significant difference in muscle function. Conclusions: US showed the FHL tendon thickening and en pointe-related vascular compromise in pre-professional dancers, even when they are asymptomatic. ABSTRACT FROM AUTHOR